Economic characteristics and significance of the oil plant sector in Serbia - Božić, Dragica; Munćan, Petar (Economics of Agriculture, 2010)
Serbia is one of the largest producers of oil crops in Europe, primarily of sunflower and soy bean. In the structure of harvested surfaces under oil crops in Serbia (amounting in the last decade to over 300 000 ha) sunflower takes the frst place (almost two thirds of total surface in certain years), followed by soy bean. The lowest share in harvested surfaces under oil crops has the rapeseed, whereas the production of oil pumpkin is only just starting. Increased demand for oil plants on international market in recent years caused significant increase of prices which reflected on the production of these plant cultures. Objective of this paper is the analysis of the most important economical characteristics and contribution of the oil crops sector to the economical development of Serbia in the period 2000-2008. Principal indicators of the significance of a sector in the total economical development of Serbia were analyzed, share in the Gross Added Value, employment and export. Economical efficiency of the production of main oil crop cultures (sunflower and soybean) on family agricultural households in Serbia has been established. Main sources of data were publications and internal documents of the Statistical Office of the Republic of Serbia. Calculations of Gross margin which were used to consider economical efficiency of the oil crops production were composed based on elements gathered in performed survey. Survey was performed on 50 selected family agricultural households which are exclusively engaged in crop production.